1986
DOI: 10.2466/pr0.1986.59.2.943
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Relationship between Anxiety about Mathematics and Performance

Abstract: 92 students in an upper level college statistics course were given a number of mathematics anxiety and performance measures. A canonical analysis resulted in one significant canonical factor, labeled Mathematics Efficiency, which explains the relationship between mathematics anxiety and mathematics performance. Variables making the greatest contribution to this high math efficiency factor were mathematics anxiety and attitude toward mathematics. One major implication of these results is that psychologists need… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
42
0
2

Year Published

1993
1993
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 10 publications
0
42
0
2
Order By: Relevance
“…Adams and Holcomb (1986) identified a construct they called mathematics efficiei~cy to explain the correlation; and Hadfield and Maddux (1988) indicated that cogi~itive style (i.e., whether or not the student was field dependent) was an intermediary factor. However, all of these expect that mathematics anxiety is a causative agent of the third factor, rather than the third factor causing both the mathematics anxiety and the poor performance in mathematics.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Adams and Holcomb (1986) identified a construct they called mathematics efficiei~cy to explain the correlation; and Hadfield and Maddux (1988) indicated that cogi~itive style (i.e., whether or not the student was field dependent) was an intermediary factor. However, all of these expect that mathematics anxiety is a causative agent of the third factor, rather than the third factor causing both the mathematics anxiety and the poor performance in mathematics.…”
Section: Resultsmentioning
confidence: 99%
“…A moderate but significant negative correlation between the two has been observed by many researchers (Adams & Holcomb, 1986;Betz, 1978;Brush, 1978;Cooper & Robinson, 1991;Cowen, Zax, Klein, Izzo, & Trost, 1963;Dew, Galassi, & Galassi, 1984;Lunneborg, 1964;Resnick, Viehe, & Siegel, 1982;Suinn, Edie, Nicoletti, & Spinelli, 1972;Wigfield & Meece, 1988). However, it should be noted that the observations of Hunsley (1987) using multiple regression, and those of Hadfield and Maddux (1988) using analysis of variance, did not indicate a significant relationship between the two.…”
mentioning
confidence: 99%
“…Richarson and Suinn (1972) reported that many people who do not suffer from general anxiety do suffer from anxiety about mathematics. Consistent, negative relationships between mathematics anxiety and performance have been established (Adams & Holcomb, 1986;Aiken, 1970Aiken, , 1976Betz, 1978;Gliner, 1987;Szetela, 1973). The Phobos (Ferguson, 1986) was developed to measure mathematics anxiety.…”
mentioning
confidence: 99%
“…In fact, many students have a listless behavior to research and do not worry about how and why they have to carry it. As claimed by Adams & Holcomb (1986), Elmore & Vasu (1980) and Wise (1985), students at the undergraduate university level, typically tend to view research and research teaching courses with negative attitudes.…”
Section: Doing Research Is Not An Easy Activity As Wernher Von Braunmentioning
confidence: 99%
“…Students think that it is tough and dry to study the research (Adams & Holcomb, 1986). They do not understand the concepts of research and its importance in their professional life.…”
Section: Doing Research Is Not An Easy Activity As Wernher Von Braunmentioning
confidence: 99%